2019
DOI: 10.1080/02601370.2019.1567613
|View full text |Cite
|
Sign up to set email alerts
|

The search for security in precarious times: non-traditional graduates perspectives on higher education and employment

Abstract: This article explores non-traditional student and graduate views of the university in Ireland and Portugal as it relates to their expectations of, and experiences in, the labour market. The research is based on in-depth biographical interviews with 61 non-traditional students and graduates conducted longitudinally (85 interviews in total). The article contextualises the research in relation to the expansion of higher education internationally as well as national and EU policies aimed at supporting a 'knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…We then provide an example of how critical social theory informs our research on multiliteracies using a Freire's work on a pedagogy of hope. Finnegan et al (2019) share five case studies of graduates, defined as non-traditional learners, a category that includes individuals 'with disabilities, mature students, and students from working class and particular ethnic backgrounds' (p. 157). They delve into the impact of neoliberal perspectives that shape both government policies and participants' experiences to develop their analysis, which was informed by a critical realist approach that involved working 'between grounded empirical research and systematic theoretical investigation of the socio-historical context ' (p. 162).…”
Section: Arguesmentioning
confidence: 99%
See 1 more Smart Citation
“…We then provide an example of how critical social theory informs our research on multiliteracies using a Freire's work on a pedagogy of hope. Finnegan et al (2019) share five case studies of graduates, defined as non-traditional learners, a category that includes individuals 'with disabilities, mature students, and students from working class and particular ethnic backgrounds' (p. 157). They delve into the impact of neoliberal perspectives that shape both government policies and participants' experiences to develop their analysis, which was informed by a critical realist approach that involved working 'between grounded empirical research and systematic theoretical investigation of the socio-historical context ' (p. 162).…”
Section: Arguesmentioning
confidence: 99%
“…Working at jobs that do not pay well, lack benefits, job security, and a clear pathway to advancement, often leads to a sense of anxiety, powerlessness, and a lack of confidence over one's future. Finnegan et al (2019) note that in a neoliberal context, this failure to attain permanent, well-paid employment is attributed to individual success (or lack thereof) rather than the broader socio-economic conditions, so that 'the 'responsibilised subject' is tasked with resolving social problems and overcoming risks on their own' (p. 160).…”
Section: Arguesmentioning
confidence: 99%
“…Precarity for adult educators may be extensive but it is certainly not a new occupational condition when we note the references made to it in the Green paper (Department of Education and Science 1998), White paper (Department of Education and Science 2000) and even the Murphy report of 1973 (Committee on Adult Education 1973). Indeed, there has been much more focus in recent years on precarity and its impact across occupational fields (Bobek, Pembroke, and Wickham 2018;Courtois and O'Keefe 2015;Finnegan et al 2019;Standing 2011). Although a phenomenon originally associated with low-status unqualified work, precarious work has spread to what were once regarded the 'safe and stable' professional fields such as teaching (Bobek, Pembroke, and Wickham 2018).…”
Section: Precarity and Uncertain Occupational Futuresmentioning
confidence: 99%
“…There has been some response to precarity in Ireland by unions and activist groups and there is a small but growing body of literature around graduate precarity. For example, a recent transnational biographical research project (Finnegan et al 2019) has shown that mature graduates, and the nontraditional graduate population in general, face an additional set of barriers in their quest for the decent and stable work that traditional graduates access with more ease. Lack of access to social networks or capital; caring responsibilities; financial hardships; geographic immobility can all conspire to contract career opportunities for many non-traditional graduates.…”
Section: Precarity and Uncertain Occupational Futuresmentioning
confidence: 99%
“…Расширение глобальных производственно-сбытовых цепочек привело к росту занятости в неформальной экономике за счет скрытых и часто многосторонних трудовых отношений, которые в значительной степени не признаются действующим законодательством о труде и системой социальной защиты [4,5]. Конкретные экономические и политические условия, связанные с неолиберализмом, сделали течение современной жизни не только нестабильным, но и небезопасным в течение длительных периодов времени и в будущем [6]. Быстрый рост цифровых технологий стимулировал «экономику рабочих мест», которая предлагает специализированные и неспециализированные рабочие места через цифровые онлайн-платформы, но без стандартных отношений между работодателем и сотрудником [7].…”
Section: Introductionunclassified